CERD and the Native Title Amendment Act 1998 : sixteenth report of the Parliamentary Joint Committee of Native Title and the Aboriginal and Torres Strait Islander Land Fund. - Australia. Parliament. Joint Committee on Native Title and the Aboriginal and Torres Strait Islander Land Fund. ([Canberra] : Parliament of the Commonwealth of Australia, 2000)
The Committee has examined the findings of the United Nations Committee on the Elimination of Racial Discrimination and concluded that the amendments to the Commonwealth's Native Title Act are consistent with Australia's obligations under the Convention on the Elimination of All Forms of Racial Discrimination.
Includes bibliographical references.
Also available online
Keywords: Australia; International Convention on the Elimination of All Forms of Racial Discrimination -- (1966); Race discrimination -- Australia; Native title - Law and legislation - Commonwealth; Race relations - Racial discrimination - Legislative; Australia